Urban food retailing and food prices in Africa: the case of Addis Ababa, Ethiopia - Assefa, Thomas; Abebe, Girum; Lamoot, Indra; Minten, Bart (Emerald Publishing Limited, 2016)
Despite the large interest in urban food markets, there are, however still relatively few good studies that have empirically documented the functioning of retail markets in developing countries, especially in Africa. The purpose of this paper is to look in particular at the case of Addis Ababa, a city of more than four million people and the capital of Ethiopia, one of the most populous countries in Sub-Saharan Africa. To better understand urban food retail, the authors rely on a large primary survey.To better understand urban food retail, the authors rely on a large primary survey. Based on a stratified sampling scheme representative for the city as a whole, 1,226 urban food retail outlets were interviewed in March and April 2012.The authors find increasing differentiation in food retail markets in recent years. Despite the prohibition of foreign direct investment in food retail, a domestic modern private retail sector is quickly emerging. However, its share is still very small and, in contrast to roll-outs of modern retail in other countries, it has not yet entered the cereal sector, which remains in the hands of local flour mills, cereal shops, and cooperative retail outlets. The importance of cooperative retail is growing even more rapidly. It is especially important for those products where supply chains are controlled by the government. On the high-end, domestic private modern retail outlets deliver high-quality products at significantly higher prices,ceteris paribus. At the other side, the authors see cooperative retail that delivers food at significantly lower – and subsidized – prices. However, the latter shops are characterized by typical price control problems, reflected in regular lack of supplies and queuing.The study is limited to the city of Addis Ababa and it seems useful if similar studies could be conducted in other cities in Africa.Despite the large interest in urban food markets, there are still relatively few good studies that have empirically documented the functioning of retail markets in developing countries, especially in Africa. The paper therefore contributes to fill this lacuna by studying urban food retail markets using new and unique data for Africa.